A critical parametric review of polymers as shale inhibitors in water-based drilling fluids - Abbas, M.A. (Elsevier B.V., 2021)
Wellbore stability is essential to be maintained during drilling operation. It is on target due to many issues among them shale hydration is most critical problem using water-based drilling fluids especially. The reactive clay minerals of shale have greater affinity towards water and show swelling when interact with water and make wellbore conditions unstable. Different inhibitors have been utilized to inhibit water invasion. Among them, polymers proved to be efficient and biodegradable. In this paper, responsible clay minerals for hydration and their reactivity towards water is explained. The parametric mechanism of hydration and inhibition are thoroughly reviewed. In this review paper, the inhibition performance parameters of polymers are presented. Polymers utilized in WBDF are critically reviewed with respect to their inhibition ability based on the performance parameters like electrostatic interaction, hydrogen bonding with clay minerals, thermal stability, and their effect on drilling fluid rheology. Different researchers have explained some of the parameters. But they are found to be insufficient to explain all the important parameters. There are other parameters to investigate the polymer's performance that are required to be explained for an efficient inhibition. These parameters are electronegativity difference in the active site of polymer, hydrophobicity, concentration, and agglomeration. These parameters are also important to discuss because they affect polymer's performance and drilling fluid's rheological properties. Nanoparticles have been used for inhibition with polymers and their effectiveness to plug nanopores is also reviewed. Some of the polymers were found to be unstable and contaminating nanoparticles. The reason behind this problem have also been explained parametrically here. The limitations of utilized polymers have been discussed in this paper w.r.t. performance parameters. Polymer performance and characterization results are presented and evaluated w.r.t. to performance parameters. Future perspective for a better inhibition performance is the utilization of a polymer with improved performance parameters. Â© 2021 Elsevier B.V.